Effects of plant proteins as food on growth performance, carcass quality and plasma biochemical parameters of Beluga juvenile (Huso huso) - Taghizadeh, V.; Imanpoor, M.R.; Asadi, R.; Chamanara, V.; Sharbati, S. (2011)
The possibility of replacing fish meal with plant protein sources (soybean meal and corn gluten) for beluga (initial body mass 159.55±2.14g) was studied in autumn 2009. Experimental feeds with 46.5% of crude protein, GE: 5.4 Cal g -1 in four replacement levels: 0, 270, 450 and 660 gr kg 1 were prepared and fish were fed on the diets for 60 days. Significant differences were found in growth performance (P<0.05) of different diets. Biomass gain, specific growth rate, feed conversion rate and protein efficiency ratio in fish feed with diet 1 was higher (P<0.05) that the other ones. However, growth performance in diets 2 and 3 were not significantly different (P>0.05). Moisture of beluga carcass fed with diet 4 was significantly higher (P<0.05) that the other diets. However, protein, fat and ash were not significantly different (P>0.05) among diets. The hematocrit percentage was significantly higher in experimental treatments 1 and 2 than 3 and 4 and the plasma glucose was significantly different between diets 1 and 4 (P<0.05). With decreased fish meal, significantly (P<0.05) decreased plasma cholesterol was found in diet 1 compared to the diets 3 and 4. Results showed that combination of soybean meal and corn gluten is not a good substitute for fish meal and deceased growth performance of the fish. Published